Spatial distribution characteristics and influencing mechanisms of sports facilities in urban areas: evidence from Tianhe District, Guangzhou - Lao, Xiaomin; Zhu, Siting; Xiong, Bo; Yin, Hui (Frontiers in Built Environment, 2026)
In recent years, with the accelerated pace of global urbanization and a substantial increase in public health consciousness, sports facilities have far - reaching implications for the quality of life of residents. This study selects Tianhe District in Guangzhou as a case and explores the spatial distribution characteristics and influencing mechanisms of sports facilities through the application of GIS spatial analysis methods, the network dimension model, and the Geodetector. The findings are as follows: (a) The overall spatial pattern presents a distribution of “dense in the west and sparse in the east; dense in the south and sparse in the north”, featuring a multi - centered agglomeration pattern, mainly concentrated in areas such as Tianhe South Subdistrict and Linhe Subdistrict. (b) The facilities are arranged in a compact manner, with an average distance of less than 500 m, yet the distribution demonstrates a significant imbalance. (c) Human factors exert a significantly stronger influence on spatial differentiation compared to natural factors. Among them, transportation distance has the most substantial impact, while topography has the weakest influence. Moreover, the results of interaction detection reveal an enhanced interactive influence between pairwise factors on the spatial distribution of sports facilities. This research offers a scientific basis for optimizing urban sports facility planning and balancing resource allocation, significant for promoting high-quality urban public service development.